2014
DOI: 10.1007/s10147-014-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Different clinicopathological features between patients who developed early and late recurrence following surgery for renal cell carcinoma

Abstract: The risk factors for clinical recurrence differed according to the time that had elapsed between initial surgery and the first metastasis in patients with localized renal cell carcinoma. Our study showed age at initial surgery and the pT stage were independent predictive factors for late recurrence. Further investigation of a larger number of patients is required to predict which patients may develop recurrence in the future and to choose appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…The latest study on Japanese patients by Fujii et al . showed the following parameters to be independent predictive factors of ER: positive symptoms at diagnosis, ≥pT2, positive lymphovascular invasion and histological grade 3; these results were similar to those of Kobayashi et al . However, both Kroger et al .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The latest study on Japanese patients by Fujii et al . showed the following parameters to be independent predictive factors of ER: positive symptoms at diagnosis, ≥pT2, positive lymphovascular invasion and histological grade 3; these results were similar to those of Kobayashi et al . However, both Kroger et al .…”
supporting
confidence: 85%
“…However, both Kroger et al . and Fujii et al . did not include patients without recurrence after 5 years of radical surgery.…”
mentioning
confidence: 99%
“…However, how the conversion of disseminated dormant tumor cells to a proliferative state is regulated is still uncertain. Nonetheless, regulation of the growth from dormant tumor cells may be explained in part through the interaction of the tumor cells with their microenvironment, limitations in vascular supply, or an active immune system [25,30]. Thus, it may take years before such dormant tumor cells become detectable metastatic sites, depending on the immunogenic status of dormancy [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that patients with early recurrence showed poor cancer-specific survival (CSS) after recurrence compared with those with late recurrence. Fujii et al [25] evaluated the clinicopathological characteristics and identified risk factors in patients with early recurrence (≤ 5 years, n = 77) and late recurrence (> 5 years, n = 18) following initial surgery for renal cell carcinoma. They found that patients with early recurrence had higher stage, higher grades and more LVSI compared with those with late recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the characteristics between the E-group and the L-group, mitotic count was significantly lower in the L-group than that in the E-group. With respect to the relationship between the degree of tumor malignancy and TTR, Fujii et al [21] showed that a lower pathological T stage was significantly more common in the late-recurrence group (after 5 years from resection) than in the early-recurrence group (within 5 years from resection) in patients with renal cell carcinoma. Oven et al [22] also showed a similar tendency in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%